Methods Effectiveness of Using Learning Methods in Improving Student Learning Outcomes - Rakhmawati, A; Fadhilah, Fadhilah (Islamic Education Department, Islamic University of Majapahit (Universitas Islam Majapahit) Mojokerto, Indonesia, 2024)
To build quality human resources, education is very important. There is a need for more inventive learning approaches because educational challenges in the modern era are increasingly complex. This study discusses how traditional and modern learning methods differ in terms of improving student learning outcomes. This research uses comparison and analysis of previous research journals. The research results show that traditional learning methods, although easy to use, tend to be one-way and can reduce student engagement. In contrast, modern methods, such as project-based and collaborative learning, increase student interactivity and motivation and increase learner engagement.